Study on the Wear Resistance of Duplex Stainless Steel after Undergo Nitrogen Diffusion Process Varies With Time - Shahrom, Mohammad Firdaus (Universiti Teknologi Petronas, 2011)
This report basically discusses the research study on the wear resistance of duplex stainless steel after undergo nitrogen diffusion process varies with time. This report consists of the project's background, objectives, and problem statements, scope of work, literature review, methodology or the flow of the project, result & discussion and last but not least the conclusion. In this work the author report a study on the wear resistance of duplex stainless steel (DSS) after undergo nitriding process which will be conducted in a horizontal tube furnace and being conducted at four different times. Nitriding is one of the traditional thermochemical treatments for surface engineering that can be utilized in order to harden the duplex stainless steel surface to resist any failure. It wills also affecting the wear resistance of the steel. Wear characteristics are more to system properties rather than material properties. Contact type, the operating conditions, environment, the material characteristics of the test material and the mating material are the main factors for operating wear mechanism. In order to conduct the nitriding process, it is crucial to highlight the important of its variables such as time, temperature and gas velocity. However, for this project, the author will investigate and identifY the effect of changing the time for nitriding process towards the wear resistance. Therefore, the result for before (raw sample) and after nitriding sample which are varies in time ( 1.0 hour, 2.5 hour, 4.5 hour) will being compared and observed. This objective will be achieved by a series of laboratory tests which is "wear test" using pin-on-disk method will be used to analyze the wear characteristic using DUCOM Multi Specimen Tester. To prove and verifY that the nitriding process is successfully, metallographic study which using XRD machine will be done.